A narrative account of legislated social security changes for Germany - Gechert, Sebastian; Paetz, Christoph; Villanueva, Paloma (Düsseldorf, 2016)
"Exploiting official historical records of the German Bundestag and Bundesrat, the Federal Ministry of Labour and Social Affairs and the German statutory pension insurance scheme, we construct a narrative of legislated social security changes for Germany between 1970 and 2013 in order to identify important discretionary shocks to the social security system. The historical account covers major changes in transfers and social security benefits and contributions for pensions, health care, long-term care and unemployment insurance on the German federal level and thus complements the tax narrative of Uhl (2013). Based on the provided information we are able to code a rich bottom-up time-series of fiscal policy shocks for empirical macroeconomic analysis, addressing the identification problem. Therefore, we collect information regarding the underlying motivation, the dates of the legislative process and the prospective financial impact, closely following the methodology of Romer and Romer (2010) and Uhl (2013)."